Synthesis of nanostructured CO3O4 as anode materials for lithium-ion batteries. - Sim, Hon Yew. (2010)
Cobalt oxide (Co3O4) nanoparticles were synthesized by a simple surfactant-assisted method. The influence of reaction parameters such as different cobalt precursors, amount of surfactant (PVP) added, different ratio of reaction medium and NaOH concentration was investigated via several characterization techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). Different morphologies of Co3O4 were obtained – regular hexagonal nanodiscs, perfect cubical nanocubes and nanoflowers were readily synthesized from the different designed parameters of a reaction system. Among nanocubes, nanodiscs and nanoflowers that were tested for their electrochemical properties, nanodiscs give the highest lithium storage capacity during extended cycling.